2011
DOI: 10.1371/journal.pone.0022047
|View full text |Cite
|
Sign up to set email alerts
|

SPARC, FOXP3, CD8 and CD45 Correlation with Disease Recurrence and Long-Term Disease-Free Survival in Colorectal Cancer

Abstract: BackgroundSPARC is a matricellular protein involved in tissue remodelling, cell migration and angiogenesis, while forkhead box P3 (FOXP3) protein functions as a transcription factor involved in immune cell regulation. Both SPARC and FOXP3 can play an anti-tumorigenic role in cancer progression. The aim was to determine if SPARC, FOXP3, CD8 and CD45RO expression levels are associated with colorectal cancer (CRC) stage, disease outcome and long-term cancer-specific survival (CSS) in stage II and III CRC.Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 32 publications
(50 reference statements)
6
43
1
Order By: Relevance
“…Immune system invasion and/or escape is essential in the etiology of lung adenocarcinoma, and the presence of tumor-infiltrating lymphocytes (TILs) in the tumor microenvironment is an indication of the host immune response to tumor antigens (8). TILs comprise a variety of immune cells, including CD4 + T lymphocytes, CD8 + lymphocytes, FOXP3 + regulatory T cells, natural killer (NK) cells, dendritic cells and macrophages (9). TILs are attracting attention for their use in monitoring the immune response in the tumor microenvironment and predicting the prognosis and treatment response in several cancers, such as colorectal and breast cancers (8,9).…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Immune system invasion and/or escape is essential in the etiology of lung adenocarcinoma, and the presence of tumor-infiltrating lymphocytes (TILs) in the tumor microenvironment is an indication of the host immune response to tumor antigens (8). TILs comprise a variety of immune cells, including CD4 + T lymphocytes, CD8 + lymphocytes, FOXP3 + regulatory T cells, natural killer (NK) cells, dendritic cells and macrophages (9). TILs are attracting attention for their use in monitoring the immune response in the tumor microenvironment and predicting the prognosis and treatment response in several cancers, such as colorectal and breast cancers (8,9).…”
Section: Original Articlementioning
confidence: 99%
“…TILs comprise a variety of immune cells, including CD4 + T lymphocytes, CD8 + lymphocytes, FOXP3 + regulatory T cells, natural killer (NK) cells, dendritic cells and macrophages (9). TILs are attracting attention for their use in monitoring the immune response in the tumor microenvironment and predicting the prognosis and treatment response in several cancers, such as colorectal and breast cancers (8,9). Therefore, in the present study, we proposed that the infiltration of lymphocytes in lung adenocarcinoma and expression of chemokine receptors might be correlated with tumor differentiation, TNM stage, clinical stage, disease-free survival (DFS) or overall survival (OS).…”
Section: Original Articlementioning
confidence: 99%
“…However, the clinical significance of FOXP3 expression in tumor cells by immune histochemical analysis is still not concluded in human cancers, but evidence revealed a strong correlation between FOXP3 expression and metastasis [73]. A better disease outcome and survival was related to patients with both FOXP3+ and HER2+ breast cancer [17] and colorectal cancer [74], and a poor disease outcome or metastasis in patients with breast cancer [75], colorectal cancer [76], non-small cell lung cancer [77], urinary bladder cancer [78], hepatocellular carcinoma [79], esophageal squamous cell carcinoma [80], tongue squamous cell carcinoma [81], melanoma [82] and gliomas [83], but no significance in patients with non-small cell lung cancer [84]. However, recent clinical observations in larger sample cohorts with more than 1,000 patients have indicated that nuclear FOXP3 expression in tumor cells predicts better survival in breast cancer patients and they reported that essentially all FOXP3 in breast tumor cells is cytoplasmic [17,18,20].…”
Section: The Variety Of Foxp3 Function and Its Clinical Implicationsmentioning
confidence: 99%
“…This contradiction calls for further studies aimed to reappraise FoxP3 + cells role in CRC, but also underlines the methodological issue of T cells topographic assessment 56 . More recently, Chew et al investigated whether Secreted Protein Acidic and Rich in Cysteine (SPARC), a matricellular protein involved in tissue remodeling, cell migration and angiogenesis, FoxP3, CD8 and CD45RO expression levels were associated with CRC stage, disease outcome and long-term cancer specific survival (CSS) in stage II and III 57 . They found that high levels of SPARC and FoxP3 protein (which seems to have an anti-tumorigenic role in cancer progression) were associated with better disease outcome in stage II CRC and may be prognostic indicators of CSS.…”
Section: Wwwintechopencommentioning
confidence: 99%